Analisis Yuridis Perbuatan Wanprestasi atas Sengketa Pendaftaran Peralihan Hak atas Tanah dalam Jual Beli Tanah (Studi Putusan Nomor 27/PDT.G/2023/PN BJB) - Rizka Putri Siregar; Hasim Purba; Rosnidar Sembiring (Jurnal Hukum Lex Generalis, 2025)
The sale and purchase of land that has not been followed by the transfer of land ownership certificates creates legal risks such as weak ownership, the loss of the buyer’s rights over the land, and the absence of guaranteed legal certainty and protection. This research employs a normative juridical method with a descriptiveanalytical approach. The results of the study indicate that land sale and purchase agreements in Indonesia represent an agreement between the seller and the buyer that gives rise to rights and obligations to transfer ownership rights. The juridical analysis of the judge’s considerations in Decision No. 27/Pdt.G/2023/PN Bjb shows that the sale and purchase of land is considered valid as a civil agreement because the legal requirements of a contract under Article 1320 and Articles 1457-1458 of the Civil Code have been fulfilled, namely mutual consent, legal capacity of the parties, a specific object, and payment of the agreed price.